E-bikes in the Mainstream: Reviewing a Decade of Research. Issue 1 (2nd January 2016) - Fishman, Elliot; Cherry, Christopher
Abstract : Electric bicycles (e-bikes) represent one of the fastest growing segments of the transport market. Over 31 million e-bikes were sold in 2012. Research has followed this growth and this paper provides a synthesis of the most pertinent themes emerging over the past on the burgeoning topic of e-bikes. The focus is transport rather than recreational e-bike research, as well as the most critical research gaps requiring attention. China leads the world in e-bike sales, followed by the Netherlands and Germany. E-bikes can maintain speed with less effort. E-bikes are found to increase bicycle usage. E-bikes have the potential to displace conventional motorised (internal combustion) modes, but there are open questions about their role in displacing traditional bicycles. E-bikes have been shown to provide health benefits and an order of magnitude less carbon dioxide than a car travelling the same distance. Safety issues have emerged as a policy issue in several jurisdictions and e-bike numbers are now approaching levels in which adequate safety data are able to be collected. Research on e-bikes is still in its infancy. As e-bike usage continues to grow, so too will the need for further research, in order to provide the necessary data to inform policy-makers and industry.